[Translated article] Surgical treatment of non-displaced subcapital hip fracture: Femoral Neck System vs. cannulated screws. Comparative study - P. Lalueza-Andreu; Á. Martínez-García; P. Checa-Betegón; J. García-Coiradas; J.A. Valle-Cruz; F. Marco-Martínez (Revista Española de Cirugía Ortopédica y Traumatología)
Objective: The objective of this study is to compare the outcomes of using the Femoral Neck System (FNS) (DePuy Synthes®) versus the use of cannulated screws (CS) in the surgical treatment of non-displaced subcapital hip fractures. Materials and methods: A retrospective cohort study was conducted on non-displaced subcapital hip fractures treated with CS or FNS between 2020 and 2023, with a minimum follow-up of one year. A total of 28 patients were included, 14 treated with CS and 14 with FNS. Demographic, radiological, clinical, and functional variables were analyzed. Results: In the CS group, 64% were male, with a mean age of 66.5 years (SD 14.9) and an average follow-up of 22 months (range, 12-36 months). In the FNS group, 57% were male, with a median age of 60.8 years (SD 13.78) and an average follow-up of 16 months (range, 12-24 months).Regarding functional outcomes, no significant differences were found between FNS and CS in the Harris scale: 94.21 ± 11.55 for FNS and 96.50 ± 6.9 for CS (p = 0.618).The total postoperative complications (FNS/CS) were 7.1% versus 43%, and implant failure with conversion to total hip replacement was 0% versus 43%, both significantly higher in the CS group (p = 0.047; p = 0.016, respectively). The FNS also presented a lower rate of avascular necrosis (0% versus 11.1%, p = 0.391) and nonunion (0% versus 20%, p = 0.163), although these differences did not reach statistical significance. Conclusions: Although both treatment methods, cannulated screws and the FNS, showed similar short-term functional outcomes in the management of undisplaced subcapital femoral fractures, the FNS demonstrated a significantly lower rate of complications and reoperations. These results suggest that the FNS could be considered a safer and more effective option compared to cannulated screws. Resumen: Objetivo: El objetivo de este estudio es comparar los resultados del uso del dispositivo Femoral Neck System (FNS) (DePuy Synthes®) frente al empleo de tornillos canulados (TC) en el tratamiento quirúrgico de fracturas subcapitales de cadera no desplazadas. Material y métodos: Se realizó un estudio de cohortes retrospectivo sobre fracturas subcapitales de cadera no desplazadas tratadas con TC o con FNS entre los años 2020 y 2023, con un seguimiento mínimo de un año. Se incluyeron 28 pacientes: 14 tratados con TC y 14 con FNS. Se estudiaron variables demográficas, radiológicas, y resultados clínicos y funcionales. Resultados: En el grupo TC, el 64% fueron varones con una edad media de 66,5 años (DE: 14,9) y un seguimiento medio de 22 meses (rango: 12-36 meses). En el grupo FNS, el 57% fueron varones, con una mediana de edad de 60,8 años (DE: 13,78) y un seguimiento medio de 16 meses (rango: 12-24 meses).En relación con los resultados funcionales, no se encontraron diferencias significativas entre FNS y TC en la escala de Harris: 94,21 ± 11,55 para FNS y 96,50 ± 6,9 para TC (p = 0,618).Las complicaciones postoperatorias totales (FNS/TC) fueron del 7,1% frente al 43%, y el fracaso del implante con conversión a PTC fue del 0% frente al 43%, siendo significativamente superiores en el grupo de tornillos canulados (p = 0,047; p = 0,016, respectivamente). El FNS también presentó una menor tasa de necrosis avascular (0% frente al 11,1%, p = 0,391) y seudoartrosis (0% frente al 20%, p = 0,163), aunque sin alcanzar significación estadística. Conclusiones: Aunque ambos métodos de tratamiento, los tornillos canulados y el sistema FNS, mostraron resultados funcionales similares a corto plazo en el manejo de fracturas subcapitales no desplazadas de cadera, el FNS presentó una tasa significativamente menor de complicaciones y reintervenciones. Estos resultados sugieren que el sistema FNS podría considerarse una opción más segura y efectiva en comparación con los tornillos canulados.